Ready-meal consumption in older people: association with obesity and dietary intake - Soriano, Gaëlle; De Barreto, Philippe Souto; Rolland, Yves; Plessz, Marie; Goisser, Sabine; Guyonnet, Sophie; Fougère, Bertrand; Vellas, Bruno; Andrieu, Sandrine; Sourdet, Sandrine (Aging Clinical and Experimental Research, 2019)
Objective: To investigate ready-meal consumption trends in older French people, its association with overall diet quality and obesity. Design: Cross-sectional analysis Setting: Multidomain Alzheimer Preventive Trial (MAPT), France Subjects: 421 MAPT participants (mean age 76.8 years) who filled a food frequency questionnaire. Results: The frequency of ready-meal consumption was low, with nearly 90% of participants declaring consuming ≤ 1 ready-meal per week. Compared to non- and low-consumers (≤ 1 ready-meal/week), regular consumers (≥ 2 ready-meals/week) were older (p < 0.01), more often frail and pre-frail (p 0.04), with impaired cognition (p = 0.02) and functional status (p = 0.02), with more depressive symptoms (p = 0.03) and more difficulties with preparing meals (p = 0.01). Results from multivariate analyses showed that regular ready-meal consumption was not associated with obesity (p = 0.26) and diet quality (p = 0.37). Conclusions: In our sample, few older people declared consumption of 2 or more ready-meals per week, this consumption was not associated with a higher prevalence of obesity or a lower diet quality, despite the fact that these subject were older, with a lower physical and cognitive status. These findings suggest that, for these people with difficulties in meal preparation, convenience foods consumed occasionally could help to maintain diet quality and weight status.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Cooking difficulty; Diet quality; Obesity; Older; Ready-meal